Evaluation of corneal tissue changes after collagen cross-linking with ultraviolet and riboflavin A: Application of corneal tissue changes after CXL - Xing, Huaping; Oyang, Hua (Cellular and Molecular Biology, 2022)
This study was performed to evaluate the histological changes in the cornea after accelerated collagen crosslinking. In this regard, the right eyes of 7 New Zealand albino rabbits weighing 1.5 to 2 kg were studied. The right eye was considered the case group, and the left eye was considered the control group. The right eye epithelium was removed, riboflavin 0.1 solutions (10 mg riboflavin-5 phosphate in 10 ml dextran-T-500, 20%) were shaken every three minutes for 30 minutes and exposed to UVA for 10 minutes, and crosslinking was performed. All rabbits were euthanized and histologically evaluated. Apoptosis was assessed using the tunnel method. The results showed a significant difference in the mean percentage of apoptotic cells in the treatment and control groups. In both endothelial cells and keratocytes in the treated cornea, the number of apoptotic cells was significantly higher than in the control group. In the general examination of the cornea (keratocytes and endothelium) in the right eye of rabbits, the mean and standard deviation of the percentage of apoptotic cells was 18.39 ± 3.4 and in the left eye was 6.37 ± 1.8. The apoptosis results of keratocytes in the right eye showed that the mean and standard deviation for the percentage of apoptotic keratocytes was 2.86 ± 1.07, which was significantly higher than in the left eye (0.53 ± 0.43) (P <0.001). The mean and standard deviation of endothelial apoptotic cells in the right and left eyes were 86.2 and 53.5, respectively, statistically significant (P = 0.026). Although CXL is a reliable method of preventing the progression of keratoconus disease, there is still a risk of endothelial cell damage and related complications due to endothelial cell damage, and further studies are needed.